2018
DOI: 10.1016/j.ssmph.2018.09.004
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal patterns of under 5 mortality in Nigeria

Abstract: HighlightsUnder 5 mortality rates in Nigeria are very high.There are significant variations in under 5 mortality rates across states over time.There is evidence of statistically significant spatial autocorrelation over time.Significant reductions are achievable with both state and region specific measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 12 publications
1
6
0
Order By: Relevance
“…The spatial autocorrelation analysis result indicated that U5MR had a spatial dependency in 2000, 2005, 2011 and 2016 (Moran's I: 0.046, 0.047; 0.09 and 0.096, respectively at p value 0.01). This result is supported by the findings in Nigeria 32 33 and Bangladesh. 34 The spatial heterogeneity of under-five mortality clustering was detected mainly in Benishangul and Afar regions.…”
Section: Open Accesssupporting
confidence: 85%
“…The spatial autocorrelation analysis result indicated that U5MR had a spatial dependency in 2000, 2005, 2011 and 2016 (Moran's I: 0.046, 0.047; 0.09 and 0.096, respectively at p value 0.01). This result is supported by the findings in Nigeria 32 33 and Bangladesh. 34 The spatial heterogeneity of under-five mortality clustering was detected mainly in Benishangul and Afar regions.…”
Section: Open Accesssupporting
confidence: 85%
“…Similarly, the urban advantage in under-5 mortality over time prevails in SSA, and the growth of urban populations predicts the magnitude of under-5 disparities [ 55 ]. Regional differences in mortality risk can be observed in both countries with slow [ 56 ] or rapid gains in child survival or that have met the MDGs [ 48 50 , 55 , 57 , 58 ]. In Nigeria, for example, wide variations in under-5 mortality are observed across states over time, with higher levels in northern regions.…”
Section: Discussionmentioning
confidence: 99%
“…[10] determined the socioeconomic indicators contributing to child mortality in Nigeria, and surprisingly, concluded that attendance of skilled health workers during delivery was associated with an increased risk of neonatal death. [11] examined the Spatio-temporal distribution of under-five mortality rate in Nigeria and found that there is spatial clustering and geographical disparities between states in Nigeria. Recently, [12] examined the effect of spatial distribution and other covariates on under-five mortality deaths in Nigeria.…”
Section: Introductionmentioning
confidence: 99%